2019
DOI: 10.1038/s41398-018-0355-8
|View full text |Cite
|
Sign up to set email alerts
|

Cell type-specific gene expression patterns associated with posttraumatic stress disorder in World Trade Center responders

Abstract: Posttraumatic stress disorder (PTSD), a chronic disorder resulting from severe trauma, has been linked to immunologic dysregulation. Gene expression profiling has emerged as a promising tool for understanding the pathophysiology of PTSD. However, to date, all but one gene expression study was based on whole blood or unsorted peripheral blood mononuclear cell (PBMC), a complex tissue consisting of several populations of cells. The objective of this study was to utilize RNA sequencing to simultaneously profile t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
187
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 230 publications
(206 citation statements)
references
References 81 publications
14
187
4
Order By: Relevance
“…Binding of cortisol to the GR downregulates corticotropin releasing factor (CRF) expression in the hypothalamus, acting as a negative feedback of HPA‐axis activation 13 . Interestingly, in PTSD participants, the FK506 binding protein 5 (FKBP5), a chaperone protein that affects GR and mineralocorticoid receptor (MR) binding sensitivity for glucocorticoids and inhibits cellular translocation, is differentially expressed in several RNA sequencing studies compared with control participants both in peripheral blood cells, and postmortem PFC brain tissue 14‐16 . Together, these data provide strong support for the hypothesis that PTSD is associated with a persistent dysregulation in the canonical HPA‐axis stress system 4 …”
Section: Introductionmentioning
confidence: 77%
“…Binding of cortisol to the GR downregulates corticotropin releasing factor (CRF) expression in the hypothalamus, acting as a negative feedback of HPA‐axis activation 13 . Interestingly, in PTSD participants, the FK506 binding protein 5 (FKBP5), a chaperone protein that affects GR and mineralocorticoid receptor (MR) binding sensitivity for glucocorticoids and inhibits cellular translocation, is differentially expressed in several RNA sequencing studies compared with control participants both in peripheral blood cells, and postmortem PFC brain tissue 14‐16 . Together, these data provide strong support for the hypothesis that PTSD is associated with a persistent dysregulation in the canonical HPA‐axis stress system 4 …”
Section: Introductionmentioning
confidence: 77%
“…Binding of cortisol to the GR downregulates corticotropin releasing factor (CRF) expression in the hypothalamus, acting as a negative feedback of HPA-axis activation 13 . Interestingly, in PTSD participants, the FK506 binding protein 5 (FKBP5), a chaperone protein that affects GR and mineralocorticoid receptor (MR) binding sensitivity for glucocorticoids and inhibits cellular translocation, is differentially expressed in several RNA sequencing studies compared to control participants both in peripheral blood cells, and post-mortem PFC brain tissue 14,15,16 . Together, these data provide strong support for the hypothesis that PTSD is associated with a persistent dysregulation in the canonical HPA-axis stress system 4 .…”
Section: The American Psychiatricmentioning
confidence: 99%
“…These loci are not, however, the only genetic factors affecting anxiety and aggression in dogs. A recent study found a genomic area in German Shepherds, that differed between dogs having noise fear and those without noise fear 79. The same study identified genetic differences (from another chromosome) between fearful and non-fearful dogs 79.…”
Section: Genetic Factorsmentioning
confidence: 86%
“…A recent study found a genomic area in German Shepherds, that differed between dogs having noise fear and those without noise fear 79. The same study identified genetic differences (from another chromosome) between fearful and non-fearful dogs 79. In addition, a study focusing on breed differences in behavioral traits observed very high heritabilities (h 2 : 0.27–0.77) for 14 behavioral traits such as aggression and fear towards strangers, trainability, and non-social social fear, and moreover, found 131 single nucleotide polymorphism associated with behavior 80.…”
Section: Genetic Factorsmentioning
confidence: 99%